Involvement of plant signaling network and cell metabolic homeostasis in nitrogen deficiency-induced early leaf senescence - Asad, Muhammad Asad Ullah (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.